Effect of selected recovery conditions on performance of repeated bouts of intermittent cycling separated by 24 hours - Lane, K. N.; Wenger, H. A. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to examine the effects of active recovery (AR), massage (MR), and cold water immersion (CR) on performance of repeated bouts of high-intensity cycling separated by 24 hours. For each recovery condition, subjects were asked to take part in 2 intermittent cycling sessions; 18 minutes of varying work intervals performed in succession at a resistance of 80 g/kg body weight separated by 24 hours. One of four 15-minute recovery conditions immediately followed the first session and included: (a) AR, cycling at 30% VO2max; (b) CR, immersion of legs in a 15° C water bath; (c) MR, massage of the legs; and (d) control, seated rest. Results: Only the control condition showed a significant decline in the total work completed between the first and second exercise sessions (108.1 ± 5.4 kJ vs. 106.0 ± 5.0 kJ, p < 0.05). Thus, AR, MR, and CR appeared to facilitate the recovery process between 2 high-intensity, intermittent exercise sessions separated by 24 hours.